Self-Awareness as a Modality of Mental Illness Prevention in Teenagers at Zainul Hasan Islamic Boarding School, Genggong, Probolinggo - Paramita Sari; Utami Ambarsari; Yunik Windarti; Fajriatush Sholahah; Delivia Putri Manzelina; Rosda Rodhiyana (Journal of Health Community Service, 2024)
Self-awareness has been identified as a key modality in efforts to prevent mental illness in adolescents, especially those in boarding school settings. Adolescents are highly vulnerable to mental health problems such as depression, anxiety, and stress due to biological changes, environmental pressures, and social stigma associated with mental disorders. Methods: This community service activity was conducted at Pondok Pesantren Zainul Hasan, Probolinggo, using the Community-Based Participatory Research (CBPR) method. The participants consisted of 28 santris who participated in a socialization on the importance of self-awareness in preventing mental illness. This activity involved filling out pretest and posttest questionnaires to measure changes in participants' knowledge levels before and after the socialization. Results: The results showed a significant increase in santri's understanding of the concepts of self-awareness and mental health. The pre-test results showed that 20 respondents (71.5%) had a poor assessment, 5 respondents (17.8%) had a sufficient assessment, and 3 respondents (10.7%) had a good assessment of knowledge about mental health in adolescence. As for the post-test results after counseling, where 21 respondents (75%) had a good assessment, in this case there was an increase from 3 respondents to 21 respondents, an increase of 18 respondents. Conclusion: This finding confirms the importance of self- awareness education as a preventive measure in addressing mental health problems in adolescents in pesantren, where access to formal mental health services tends to be limited.